2015
DOI: 10.3390/su7032322
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality Indices for Evaluating Smallholder Agricultural Land Uses in Northern Ethiopia

Abstract: Population growth and increasing resource demands in Ethiopia are stressing and degrading agricultural landscapes. Most Ethiopian soils are already exhausted by several decades of over exploitation and mismanagement. Since many agricultural sustainability issues are related to soil quality, its assessment is very important. We determined integrated soil quality indices (SQI) within the surface 0-15 cm depth increment for three agricultural land uses: rain fed cultivation (RF); agroforestry (AF) and irrigated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 41 publications
(66 reference statements)
5
46
0
1
Order By: Relevance
“…This caused for the loss of carbon in the form of carbon dioxide [60]. Similarly, Gelaw et al [61] in a nearby site found that environmental disturbance was the main cause for the decrease in microbial biomass carbon.…”
Section: Swc Measures Mbc (Mg Kgmentioning
confidence: 91%
“…This caused for the loss of carbon in the form of carbon dioxide [60]. Similarly, Gelaw et al [61] in a nearby site found that environmental disturbance was the main cause for the decrease in microbial biomass carbon.…”
Section: Swc Measures Mbc (Mg Kgmentioning
confidence: 91%
“…The SMAF has also been successfully used in several other countries around the world [e.g., South Africa (Swanepoel et al, 2015), Ethiopia (Gelaw et al, 2015), Nepal (Kalu et al, 2015)]. The first SMAF application to Brazilian tropical soils was conducted by Cherubin et al (2016a), who verified that SMAF was effective for assessing SQ changes due to land-use change (LUC) for sugarcane expansion in the central-southern region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SMAF has been tested in other countries around the world, including South Africa (Swanepoel et al, 2015), Ethiopia (Erkossa et al, 2007;Gelaw et al, 2015), and Nepal (Kalu et al, 2015). Data from Brazilian soils was limited in the development and validation of the SMAF, and to our knowledge, no other studies using SMAF as a tool for assessing the impacts of current management practices and land uses on SQ in Brazil have been published.…”
mentioning
confidence: 99%